All about me - Rice, Melanie (Garden City, N.Y. : Doubleday, 1987)
Introduces basic concepts about the human body, everyday activities, and the world surrounding children.
Includes index.
Keywords: Children -- Juvenile literature; Human behavior -- Juvenile literature; Human behavior; Body, Human; Family life